PENGARUH KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN PADA BAGIAN PRODUKSI DI PT. ETOWA PACKAGING INDONESIA - Septerina Septerina; rusda irawati (Politeknik Negeri Batam, 2018)
Proper employee compensation will keep them motivated to improve their performance in a vigorous manner so that the results achieved from the job can give their employees satisfaction. This study aims to determine the effect of financial compensation on employee job satisfaction on the production in PT. Etowa Packaging Indonesia, to determine the effect of non-financial compensation on employee job satisfaction on the production at PT. Etowa Packaging Indonesia, and to know the influence of financial compensation and non-financial compensation simultaneously to job satisfaction of production employee at PT. Etowa Packaging Indonesia. The research design conducted by researchers is explanatory research. With a population of 253 respondents taken a sample of 171 respondents. The instrument of data collection used is observation and spreading of questionnaire. Data were analyzed using descriptive statistics and multiple regression analysis. The results stated that financial compensation and non financial compensation after tested partially or together significantly influence the employee job satisfaction in the production at PT. Etowa Packaging Indonesia.